PENGARUH PUPUK ORGANIK CAIR BONGGOL PISANG TERHADAP PERTUMBUHAN TANAMAN TEMBESU (Fagraea fragrans) - Viny Volcherina Darlis; Hasiolan Siahaan; Muhammad Mardhiansyah; Pebriandi Pebriandi (JURNAL EDUCATION AND DEVELOPMENT, 2024)
One component of the banana plant called the weevil contains macronutrients like potassium, phosphate and nitrogen. The banana weevil can be used to produce organic liquid fertilizer. Liquid organic fertilizer can be used on a variety of plants, including Fagraea fragrans, and is fertilizer in the form of a solution that contains one or more nutrients. Fagraea fragrans is a local plant in South Sumatra that offers various benefits from an ecological, economic, and cultural perspective. The purpose of this study is to identify the liquid organic fertilizer effect and concentration most conducive to promoting Fagraea fragrans plant growth. This study used a completely randomized design experimental method, with 5 treatments, control, concentrations of 20%, 30%, 40% and 50%. Parameters observed were growth of height, diameter expansion, Height gain, dry weight and top root ratio. The results showed that liquid organic fertilizer had a significant effect on promoting the growth of Fagraea fragrans on the parameters of growth of height, Height gain, dry weight and top root ratio. The best concentration of liquid organic fertilizer was 20%, with the result increase in height of 6.13 cm, dry weight of plants 1,40 g and top root ratio 3,32.